EFEKTIFITAS CACING LUMBRICUS RUBELLUS, LUMBRICUS TERRESTIS DAN EISENIA FOETIDA DALAM PEMBENTUKAN VERMIKOMPOS JERAMI PADI(Di Desa Mulung Kecamatan Driyorejo Kabupaten Gresik Tahun 2015) - Lailatul Rochma B.J; Sukiran Al Jauhari; Demes Nurmayanti (JURNAL PENELITIAN KESEHATAN, 2016)
Indonesia is among the producers of agricultural wastes, one of which being derived from rice straw. Inaddition to farming, many people raise cows, such as in Desa Mulung of Driyorejo Sub-District of GresikRegency.The purpose of the present study was to produce vermicompost from rice straw and cow manure.The present study used a pre-experiment design. It examined nitrogen contents in vermicompost usingearthworms Lumbricus rubellus, Eisenia foetida and Lumbricus terrestris.Data were analyzed descriptively byusing graphs and the results were adjusted to SNI 19-7030-2004 on Compost Specification from DomesticOrganic Waste.Results showed that Lumbricus rubellus produced nitrogen of 0.66%, Eisenia foetida 0.69% and Lumbricusterrestris 0.64%. of those three worms, the most effective one in producing excellent contents of nitrogen andthe largest amount of cocoon was Eisenia foetida. The average final weight of the worms was 1 kg and reductionwas 36-56%.In conclusion, the most effective worm in rice-straw vermicomposting was Eisenia foetida.Researchers andgovernments are recommended to inform and provide communities with training on how to producevermicompost by means of worms in order to reduce waste generation.Keywords : Vermicompost, Lumbricus rubellus,Eisenia foetida,Lumbricus terrestris